Evaluating Scrum Maturity in Point-Of-Sale Application Software Development: A Case Study of IT Financial Solutions in Indonesia - Sutan Daffa Satria Hertanto; Eko K. Budiardjo (JST (Jurnal Sains dan Teknologi), 2025)
This research is motivated by the suboptimal maturity level of Scrum implementation in Point-Of-Sale (POS) application software development at an IT Financial Solutions company in Indonesia. The unmeasured Scrum maturity level can affect the effectiveness of the development process, product quality, and delivery timeliness. This study aims to evaluate, analyze, and formulate recommendations to improve Scrum maturity in POS application development using the Scrum Maturity Model framework. This research is a descriptive case study. The research subjects were members of the development team, consisting of a Scrum Master, Product Owner, and Developer, with some of them serving as subjects in the instrument trial. The data collection method used questionnaires and documentation, with instruments based on Scrum Maturity Model indicators and interview guidelines. Data analysis was carried out using quantitative descriptive methods, including maturity-level score calculations, and qualitative analysis to strengthen the interpretation of the findings. The results of the study indicate that the Scrum maturity level is at the "Defined" level, with several aspects still in need of optimization, particularly in retrospective practices and backlog management. The conclusions of this study indicate that a structured evaluation of Scrum Maturity is effective in identifying gaps in agile practices. The implications of this research provide a strategic basis for companies to improve the quality of their software development processes continuously.